2016
DOI: 10.1111/and.12625
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of seminal mast cells in infertile men with varicocele after surgical repair

Abstract: This study aimed to assess seminal mast cells in infertile men associated with varicocele (Vx) pre- and post-surgical repair. Forty-five infertile men associated with Vx were subjected to history taking and clinical examination. In addition, semen parameters and seminal mast cells stained with 1% toluidine blue were estimated pre-varicocelectomy and three months post-varicocelectomy. Vx surgical repair revealed a significant improvement in the mean sperm concentration, progressive sperm motility, total sperm m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Lately, Mostafa et al . () reported that in infertile patients with Vx ( n = 45), there was an increased number of MCs in their semen that was significantly decreased after Vx repair.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Mostafa et al . () reported that in infertile patients with Vx ( n = 45), there was an increased number of MCs in their semen that was significantly decreased after Vx repair.…”
Section: Discussionmentioning
confidence: 99%
“…A higher number of mast cells in the interstitium and lamina propria has been associated with different causes of infertility, including varicocele 18 . In a 2017 study by Mostafa et al, a significant reduction in the number of seminal mast cells was found after varicocelectomy 19 . As mast cells and their products play a role in the pathogenesis of asthenozoospermia, it suggests a possible target for the medical treatment of infertile men.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In a 2017 study by Mostafa et al, a significant reduction in the number of seminal mast cells was found after varicocelectomy. 19 As mast cells and their products play a role in the pathogenesis of asthenozoospermia, it suggests a possible target for the medical treatment of infertile men. Therefore, drugs that could block mast cell mediator release may have a beneficial effect on sperm development.…”
Section: Discussionmentioning
confidence: 99%
“…Cincik et al reported the negative effects of seminal MCs on sperm concentration, motility, and morphology after studying 400 semen samples and staining MCs by toluidine blue‐pyronine. In varicocele, seminal MCs increasing correlates with the grade laterality of the disease but post‐varicocelectomy decreases their number in a negative correlation with sperm parameters . Tryptase after being released from MCs in the seminal fluid may reduce sperm parameters mainly motility in a dose‐ and time‐dependent manner through acting on PAR‐2 via ERK1/2 pathway …”
Section: Male Reproduction System Residing Mast Cellsmentioning
confidence: 99%